KAJIAN KERUSAKAN LINGKUNGAN PERMUKIMAN AKIBAT BANJIR DI DAERAH ALIRAN SUNGAI SANGATTA BAGIAN HILIR KABUPATEN KUTAI TIMUR PROVINSI KALIMANTAN TIMUR - , DESYELINE SUZAN KOMMALA, S.T. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research studied the settlement environmental component distruction ,which is contains of the abiotic, biotic, and cultural component, caused by flood in downstream area of Sangatta River Basin. This researchâs goals are to study the flood vulnerability level, to identify the settlements vulnerable to flood, to study the settlement environmental component distruction due to flood and to find the environmental management strategies to overcome the flood in downstream of Sangatta River Basin. The methods of collecting data were literatural study, site documentation, and interviewing the resource person. The analysis methods used quantitative analysis in accordance to flood parameter overlay analysis approximation method in terms of landform, surface drainage, slope elevation, infiltration, and rainfall, overlay analysis between floods hazardous mapping and land use mapping to determine flood risk zones, and descriptive-evaluative analysis to identify the settlement environmental component distruction due to flood. The analysis result shows that downstream area of Sangatta River Basin devided into five flood vulnerability levels which are highly vulnerable level as much as 3862.62 ha (56.66%), vulnerable level 1207.09 ha (17.71%), quite vulnerable level 1134.38 ha (16.64%), invulnerable level 261.18 ha (3.83%), and very invulnerable level 351.24 ha (5.15%). Settlement area devided into three flood vulnerability levels which are highly vulnerable level as much as 153.94 ha (28.84%), vulnerable level 354.47 ha (66.41%), and quite vulnerable level 25.36 ha (4.75%). Zoning of flood risk area consists of zone I as much as 508.41 ha (7.46%), zone II 915.93 ha (13.44%), zone III 198.32 ha (2.91%), zone IV 260.93 ha (3.83%), and zone V 4932.93 ha (72.37%). The environmental destruction take forms in inhabitant/civilian economical social activity disturbance, housing and property damage, environment and health quality degradation, farmland and embankment damage leads to crop failure, and road infrastructure damage. The environmental management strategy to overcome flood problems in downstream of Sangatta River Basin by optimizing the function of swamps as water park area, expanding production of woods such as Ramin, Meranti, Bengkirai, and other types as an alternative building material besides Ironwood to support fulfillment needs of stilt houses, and developing the concept of stilt houses as an alternative residence.